2009
DOI: 10.1142/s0192415x09006722
|View full text |Cite
|
Sign up to set email alerts
|

In vivoAnti-Cancer Activity of KoreanAngelica Gigasand its Major Pyranocoumarin Decursin

Abstract: We have reported that a 10-herbal traditional formula containing Korean Angelica gigas Nakai (AGN) exerts potent anti-cancer efficacy and identified decursin and decursinol angelate (DA) from AGN as novel anti-androgens. Here, we determined whether AGN would exert in vivo anti-cancer activity and whether decursin or DA could account for its efficacy. The AGN ethanol extract was tested against the growth of mouse Lewis lung cancer (LLC) allograft in syngenic mice or human PC-3 and DU145 prostate cancer xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 23 publications
6
64
1
1
Order By: Relevance
“…It is likely that the therapeutic effects of KH-465 are at least in part attributable to suppression of ROS production or free radical scavenging activities, with eventual beneficial effects on sperm function and spermatogenesis. Basic and clinical research has been carried out over the last few decades to explore the effectiveness of herbal medicine in treating male infertility via the improvement of sperm production, sperm quality, and libido, and reductions in oxidative stress [9]. Ginseng expected to be effective in treating male infertility by improving sperm count or motility, and by promoting DNA synthesis or protein metabolism in spermatogenic cells or Sertoli cells of the testes [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the therapeutic effects of KH-465 are at least in part attributable to suppression of ROS production or free radical scavenging activities, with eventual beneficial effects on sperm function and spermatogenesis. Basic and clinical research has been carried out over the last few decades to explore the effectiveness of herbal medicine in treating male infertility via the improvement of sperm production, sperm quality, and libido, and reductions in oxidative stress [9]. Ginseng expected to be effective in treating male infertility by improving sperm count or motility, and by promoting DNA synthesis or protein metabolism in spermatogenic cells or Sertoli cells of the testes [18].…”
Section: Discussionmentioning
confidence: 99%
“…Angelica gigas Nakai is known to exert anticancer and neuroprotective effects through apoptosis, but has also been reported to inhibit fat accumulation and to reduce adipocytokine secretion [89]. In addition, decursin, a major active component of Angelica gigas Nakai, has demonstrated a cellular antioxidant defense capacity through free radical scavenging activity in cryptorchidism-induced male infertility [1011].…”
Section: Introductionmentioning
confidence: 99%
“…Grape seed proanthocyanidins (GSPs) from Quercus petraea (Fagaceae) inhibited the growth of A549 and H1299 in mice by targeting insulin-like growth factor binding protein 3, tumor cell proliferation, and angiogenic factors (Akhtar et al, 2009). Decursin from Korean Angelica gigas (Apiaceae) (Lee et al, 2009) and 4-hydroxyderricin from Angelica keiskei roots (Kimura et al, 2004) at 50 mg/kg exerted anti-tumorigenic activity in LLCbearing mice. Similarly, two active substances, cassigarol A (Kimura et al, 2000a) and piceatannol (Kimura et al, 2000b) from Cassia garrettiana (Lauraceae) heartwood, at 50 or 100 mg/kg revealed inhibitory effects on tumor growth and lung metastasis in LLCbearing mice.…”
Section: Anti-lung Cancer Activities Of Herbal Medicines In Vivomentioning
confidence: 99%
“…aromaticum or Lobelia chinensis inhibited VEGF and angiogenesis through suppression of HIF-1α expression and Akt activation in human lung cancer cells, suggesting a possible mechanism to prevent lung cancer (Liu et al, 2005). Furthermore, a variety of natural compounds have been reported to inhibit angiogenesis via down-regulation of the MAPK signaling pathway: morellofl avone (Pang et al, 2009), thymoquinone (Yi et al, 2008a), sulforaphane (Yao et al, 2008), epoxyquinol B (Kamiyama et al, 2008), delphinidin (Lamy et al, 2008), decursin (Jung et al, 2009;Lee et al, 2009a) and 11,11′-dideoxyverticillin (Chen et al, 2005) in cancer. Our group reported that PGG diminished ERK 1/2 and JNK phosphorylation and increased phospho-p38 MAPK in a dose-dependent manner in bFGFtreated HUVECs (Huh et al, 2005).…”
Section: Molecular Targets Of Antiangiogenic Herbal Compoundsmentioning
confidence: 99%